Juridical Review of Presumed Consent as the Right of Patients in Emergency Conditions - Puspitasari, Rindy Alief; Isharyanto, Isharyanto; Purwadi, Hari (Journal of Health Policy and Management, 2019)
Background: Doctors and patients are two legal subjects who are bound in a therapeutic transaction. This transaction involves informed consent. Informed consent is the doctor's obligation and the patient's rights. There are exceptions to the application of informed consent in emergency situations. The doctor is still obliged to provide help even though the patient is in an unconscious condition and cannot give consent to the action. This is known as the Presumed Consent. This study aimed to explore presumed consent as the right of patients in emergency conditions using juridical review.Subjects and Method: This was a normative study with a law approach, case study, and conceptual approach. Legal materials used are written documents and the results of interviews. The technique of analyzing legal materials by formulating principles and legal understanding and evaluating the results of interviews. Respondents consisted of 6 General Practitioners who worked in the emergency room, ICU, treatment room, and operating room at PKU Muhammadiyah Sukoharjo Hospital.Results: According to article 17 of the medical ethics code (KODEKI) in 2012, every doctor is obliged to carry out emergency assistance as a form of humanitarian duty. This was similar to Article 51 of Law No. 29 of 2004 concerning Medical Practice. Whereas, in article 29 paragraph (1c) of Law No. 44 of 2009 concerning Hospitals it is explained that the Hospital is also obliged to provide emergency care to patients according to their abilities. If the patient is considered unable to be treated, the doctor must refer to a doctor who is more competent after giving emergency care, but if the doctor has been able to take action according to professional standards and procedures, the doctor must provide an explanation after the patient is aware or to the closest family. The results of interviews with general practitioners at Muhammadiyah Hospital in Sukoharjo, Central Java from 6 respondents all stated that patients had the right to get emergency assistance according to the standard even though without written consent from patients and families. After being aware, the patient and/or family will continue to explain information about the condition and follow-up on its handling.Conclusion: In accordance with the laws and regulations on informed consent in emergency conditions or called presumed consent, patients are entitled to immediate emergency assistance and the doctor is obliged to carry out help in accordance with professional standards and procedures. The implementation of presumed consent as a patient's right by General Physician of PKU Muhammadiyah Sukoharjo Hospital has been running according to the standard.Keywords: Emergency, Patient Rights, Presumed Consent, Juridical Review.Correspondence: Rindy Alief Puspitasari. Master Program in Law, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, 57126, Surakarta, Central Java. Email : aliefprindy@gmil.com. Mobile: +6285701587295.Journal of Health Policy and Management (2019), 4(2): 96-104https://doi.org/10.26911/thejhpm.2019.04.02.04